Foot and ankle radiographic angles in a normal saudi population - Al-Mohrej,Omar A.; Aldakhil,Sahar S.; Alsadoun,Nouf F.; Alshaalan,Fawaz N.; Alomair,Abdulrahman; Almuqbail,Bashyar; Alqahtani,Mohammed S.; Almarshad,Abdullah Y.; Al-Rabiah,Anwar M.; Alhussainan,Thamer S.; Al-Kenani,Nader S. (Journal of Musculoskeletal Surgery and Research)
Objectives: Radiographic reference lines, angles, and measures comprise the foundation for accurate evaluation and surgical planning of orthopedic surgeries, especially when it comes to foot and ankle deformities. To date, no study has evaluated the average parameters for foot and ankle radiography in the Saudi population. This study aimed to establish reference values of foot and ankle angles for the general Saudi population. Methods: We included 100 participants (200 feet) in this study, with 50 males and 50 females aged 21–30 years. We recruited subjects who had no history of foot or ankle pain, surgery or fracture, no evidence of ligamentous laxity, and no history of systemic disease. Bilateral anterior-posterior (AP) and lateral weight-bearing radiographs were obtained using standardized angles. A total of 19 angles on AP and 9 angles on lateral radiographs were evaluated. Radiographic parameters were compared between genders. Results: A total of 400 radiographs from 200 normal feet were evaluated. The mean ± SD age of the subjects was 22.7±1.7 years. Statistically significant differences in mean radiographic parameters were found between males and females in both radiographic projections. Conclusion: Significant variation exists between the normal foot and ankle reference angles between the Saudi population included in our study and other ethnicities. Moreover, significant differences are found between genders in our study. Considering the lack of other studies involving the Saudi population, the results of this study can help serve as a reference when evaluating Saudi patients.